2003
DOI: 10.1155/2003/951567
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires′ Disease ‐ Results of a Multicenter Canadian Study

Abstract: BACKGROUND: There has never been a cross-Canada surveillance project to determine the rate ofLegionellaspecies as a cause of community-acquired pneumonia requiring hospitalization and to determine whether there are any regional differences in the rates of Legionnaires' disease in Canada. Anecdotally, Legionnaires' disease is thought to be uncommon in Western Canada.METHODS: From January, 1996 through to October 31, 1997, a prospective study of the etiology of community acquired pneumonia requiring admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We observed a seasonal distribution in our study. Such an observation has already been reported in other Canadian studies [7, 28]. The reason for this pattern is currently unknown.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We observed a seasonal distribution in our study. Such an observation has already been reported in other Canadian studies [7, 28]. The reason for this pattern is currently unknown.…”
Section: Discussionsupporting
confidence: 75%
“…There are conflicting data regarding its incidence, but most studies have found Legionella spp. to be responsible for 2-5 % of acute sporadic community-acquired pneumonia [3][4][5][6][7]. These cases are believed to be acquired by inhalation of aerosolized bacteria or by microaspiration [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless we do not believe that such reporting effects would explain the magnitude in observed difference in disease burden between Toronto and the Ottawa region (itself a major site of tertiary care beds in the province). Furthermore, we believe that the wide geographic base, prolonged interval of data collection, detailed information on testing practices, and performance of all testing by a single laboratory distinguish this study from those of shorter duration conducted in Europe and the U.S. [ 11 , 26 ], and from previous Canadian sentinel surveillance efforts [ 13 ], and also provide new insights into the distinctive epidemiology of this disease in Canada's most populous province.…”
Section: Discussionmentioning
confidence: 99%
“…Both sporadic legionellosis, and large legionellosis outbreaks are known to occur in the Canadian province of Ontario [ 8 , 13 ], with over 1400 cases recorded between 1978 and 2006. However, the epidemiology of legionellosis in this region has not been reviewed previously in the biomedical literature.…”
Section: Introductionmentioning
confidence: 99%
“…While it is estimated that 97% of clinical diagnoses are obtained using a UAT [7], these tests only recognize Legionella pneumophila serogroup 1 antigens, which accounts for 50%-80% of LD cases [5]. Furthermore, the sensitivity of the test ranges from approximately 60%-100% [5,8]. Thus, it is likely that there were more cases of LD in our community in the summer of 2018 than we report here.…”
Section: Discussionmentioning
confidence: 76%